2D circularly polarized antenna array fed by spoof surface plasmonic waveguide. Issue 8 (10th June 2017) - Zheng, Chao; Qu, Shi‐Wei
Abstract: A two‐dimensional high‐gain circularly polarized (CP) patch array antenna operating in Ku band is proposed in this article. To excite a novel spoof surface plasmonic transmission line (SSP‐TL), which is mounted vertically on the ground, a waveguide with a transition are used for the momentum and impedance matching. A SSP‐TL 4‐way power divider is then used to feed a 4 × 7 circular patch array by travelling waves. Therefore, the CP radiation is generated on the patches located between the parallel SSP‐TLs. Avoiding the deterioration in axial ratio, 90° phase difference between adjacent SSP‐TLs is designed by tuning the height of the SSP‐TLs, as the dispersion property is influenced by the height of the corrugations obviously. The simulated maximum gain of 20.6 dBi is achieved at 15.2 GHz, together with the axial ratio of 0.8 dB. A prototype is fabricated and measured to validate the proposed antenna array.